EFFECT OF ZINC FORTIFIED EDIBLE COATED APRICOTS ON HEMATOLOGY IN RABBITS - M. S. Younas; M. S. Butt; I. Pasha; M. Shahid (Journal of Animal and Plant Sciences, 2015)
Worldwide, the zinc deficiency has appeared as one of the alarming issues amongst the poor nations. In current exploration, apricots were applied with edible coatings (chitosan and alginate) @ 1 and 2% along with fortification with zinc sulfate and zinc chloride @ 30 & 50 ppm concentration. The experimental diets along with a control were fed to rabbits (150 g/day/rabbit) along with normal diet in a completely randomized design for a period of 56 days. The consumption of zinc fortified chitosan and alginate coated apricots imparted substantial effect on immunity level of the body. The T-lymphocytes and hemoglobin of experimental rabbits were significantly improved by the provision of zinc fortified apricots with maximum T-lymphocytes and hemoglobin were observed in G3 (apricot containing 2% chitosan coating with 50 ppm ZnSO4) 22.34±1.29 & 13.07±0.53 % followed by G1 (apricot containing 2% alginate coating with 50 ppm ZnSO4) G4 (apricot containing 2% chitosan coating with 50 ppm ZnCl2) and G2 (apricot containing 2% alginate coating with 50 ppm ZnCl2) as 22.21±1.35 & 12.94±0.47, 22.02±1.14 & 12.78±0.45 and 21.50±1.14 & 12.61±0.51 % as comparison to G0 by 21.22±1.13 & 12.32±0.36 %, respectively. From current findings, it can be concluded that zinc fortification through edible based coating is a pragmatic approach to triumph over hidden hunger with special reference to zinc.
Keywords: Zinc fortification; Edible coatings; Chitosan; Alginate; Apricot